Shear-controlled composite cathodes for all-solid-state batteries combined synergistically with stereology-driven image analysis - Jeong, Hyeseong; Hwang, Heesu; Cho, Jeong-Won; Shin, Dongwook; Lee, Jong-Ho; Shin, Sung Soo; Hwang, Jin-Ha; Kim, Hyoungchul (Royal Society of Chemistry, 2024)
Despite the emergence of various inorganic solid electrolyte materials with high Li-ion conductivities, the advancement of electrodes for all-solid-state batteries (ASSBs) to achieve commercial-level electrochemical performance and longevity remains limited. In this study, we developed a high-performance cell through the control of shear stress and stereology-assisted quantitative microstructure analysis suitable for optimizing both cathode microstructure and interfacial resistance. Two distinct processes, uniaxial and roll pressing, were employed to assess differences in powder packing and microstructure control based on the packing technique. The roll-to-uniaxial pressed cell (RUPC) demonstrated a reduction in cathode porosity by 3.02% compared to the free-to-uniaxial pressed cell (FUPC). The initial performance of the RUPC was 162.69 mAh g-1 at 0.1C-rate, which is a 26.77% increase over the FUPC. Additionally, the interfacial area-specific resistance of the cathode active material and electrolyte in the RUPC decreased by 33.64%, from 442.92 to 149.00 Omega cm2. These results validate the effectiveness of shear stress during processing in enhancing powder packing and creating a more intimate interface. Image analysis-based microstructure characterization of the cathode composites revealed that the RUPCs after cycling exhibited a 0.44% lower porosity and a 1.67% higher electron connectivity, and 9.24% lower limited reaction interface compared to the FUPCs. The proposed cell, developed through optimized process conditions derived from comprehensive cell performance assessments and stereology-assisted microstructural quantification insights, successfully endured 520 cycles under pressurized operating conditions, with a degradation rate of 6.87% per 100 cycles from the initial discharge. Overall, our findings serve as a valuable reference for future research endeavors focusing on refining process control and conducting microstructural analyses of ASSB electrodes. Multiple optimization of composite cathodes in all-solid-state batteries is demonstrated by applying controlled shear pressure and stereology-driven image analysis.